2019
DOI: 10.1038/s41598-019-45544-x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed development of the protective IL-17A response following a Giardia muris infection in neonatal mice

Abstract: Giardia is an intestinal protozoan parasite that has the ability to infect a wide range of hosts, which can result in the clinical condition ‘giardiasis’. Over the years, experimental research has shown the crucial involvement of IL-17A to steer the protective immune response against Giardia . The development of the protective response, as reflected by a significant drop in cyst secretion, typically takes around 3 to 4 weeks. However, early-life infections often have a more ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…IL-17 triggers the production of antimicrobial peptides and complement factors, and regulates the secretion of parasite-specific immunoglobulin A (IgA) in the intestine. All these components function together in parasite clearance in the intestine [75]. In the present work a significant elevation of IL-17 level was associated with C. parvum infection in both immunocompetent and immunosuppressed compared to normal control.…”
Section: Effect Of Ntz Sec and Both In Combination On The Cytokine Profile In Immunocompetent And Immunosuppressed Micesupporting
confidence: 59%
“…IL-17 triggers the production of antimicrobial peptides and complement factors, and regulates the secretion of parasite-specific immunoglobulin A (IgA) in the intestine. All these components function together in parasite clearance in the intestine [75]. In the present work a significant elevation of IL-17 level was associated with C. parvum infection in both immunocompetent and immunosuppressed compared to normal control.…”
Section: Effect Of Ntz Sec and Both In Combination On The Cytokine Profile In Immunocompetent And Immunosuppressed Micesupporting
confidence: 59%
“…Singer & Nash showed that C57BL/6 mice provided by two vendors (later shown to differ in SFB colonization 44 ), differed in susceptibility to Giardia infection 46 . More recently, Paerewijck and colleagues demonstrated that neonate mice infected with G. muris displayed delayed IL-17A responses and parasite control 47 . As SFB colonization and the accumulation of intestinal Th17 cells typically occurs in mice at the time of weaning 48 , the delayed control of G. muris seen after neonatal infection suggests that Th17 responses triggered by these and other microbes later in life provide an environment equipped for the partial control of Giardia infections.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in support of the hypothesis that SFB may contribute at least in part to the characteristic adaptive immune response observed during Giardia infection. Interestingly, neonatal mice infected with Giardia muris fail to develop a protective IL-17A response and show delayed parasite clearance compared to adult mice ( Paerewijck et al, 2019 ). IL-17A responses and IgA production were only evident after weaning ( Paerewijck et al, 2019 ).…”
Section: Role Of the Microbiome In Giardia Pathogementioning
confidence: 99%
“…Interestingly, neonatal mice infected with Giardia muris fail to develop a protective IL-17A response and show delayed parasite clearance compared to adult mice ( Paerewijck et al, 2019 ). IL-17A responses and IgA production were only evident after weaning ( Paerewijck et al, 2019 ). Colonization of the GI tract by SFB occurs in rat and mouse hosts at the onset of the weaning process, and thus SFB populations are low in neonates, which may contribute to their inability to mount IL-17 responses and their poor resistance to Giardia infection ( Koopman et al, 1987 ; Ericsson et al, 2014 ).…”
Section: Role Of the Microbiome In Giardia Pathogementioning
confidence: 99%